The effect of pre-class assignment in enhancing the Chinese national-type school pupils in mastery Chinese language - Ling, Ke Bing; Chew, Fong Peng (Pusat Pengurusan & Pembangunan Mahasiswa, Universiti Kebangsaan Malaysia, 2021)
The KSSR curriculum system introduced by Malaysia’s ministry of education is demanding teachers to build pupils who will have the ability to carry out the learning process independently. To build pupils with the ability to learn independently, the pre-class assignment is an implementation needed to give the learning autonomy back to pupils. However, Wu (2017) stated that educators do not like students to do any pre-class assignment because they are afraid that students who have already obtained a certain level of understanding towards the learning materials would feel boring and show the signs of being not interested to listen during the in-class learning process. Thus, this study aims to study the effect of pre-class assignment in enhancing Chinese language reading comprehension mastery level of pupils from Chinese national-type schools in order to convince more educators to start practicing the use of pre-class assignment. A group of 260 pupils from eight different schools in Kuala Lumpur was involved in this study. A quantitative approach was used in this study and tests were developed and used in this study. The result of this study showed that the implementation of pre-class assignments was effective in helping pupils to master Chinese language reading comprehension. The finding of this research showed that the pupils’ performance in Chinese language reading comprehension was not affected by the language used at home and prior exposure of pupils towards pre-class assignments.